Collaborative learning in creative writing: A teacher’s perspective - Prasaja, Y. B. Agung; Pariyanto, Pariyanto; Pramesti, Tri; Nurhadi, Muizzu; Supsiadji, Mateus Rudi (Technium Social Sciences Journal, 2022)
This study aims to determine how the impact of collaborative classes on creative writing and how these classes improve students’ abilities in achieving learning outcomes. The research question that exposed is how do teachers perceive teaching creative writing through collaborative project. Collaborative learning offers a number of opportunities for students to learn interpersonal skills and character and teamwork by participating in task-oriented learning groups, so that although the content or learning materials continue to develop, collaborative groups are still able to develop various skills that can prepare students to pursue career. The method used in this study is descriptive qualitative. The primary data in this study were taken from interviews with lecturers in creative writing courses. From the analysis it can be seen that collaborative learning engages all students from diverse backgrounds personally and actively, inviting each individual to contribute knowledge and perspectives to the world of education from their own unique lives and also from their academic and vocational experiences.